2015
DOI: 10.1002/acn3.175
|View full text |Cite
|
Sign up to set email alerts
|

Identification of distinct circulating exosomes in Parkinson's disease

Abstract: ObjectiveWhether circulating microvesicles convey bioactive signals in neurodegenerative diseases remains currently unknown. In this study, we investigated the biochemical composition and biological function of exosomes isolated from sera of patients with Parkinson's disease (PD).MethodsProteomic analysis was performed on microvesicle preparations from grouped samples of patients with genetic and sporadic forms of PD, amyotrophic lateral sclerosis, and healthy subjects. Nanoparticle-tracking analysis was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 23 publications
(25 reference statements)
3
99
0
Order By: Relevance
“…Two additional proteins that are linked to PD, DJ-1 and LRRK2 are also detected in EVs isolated from urine samples from PD patients, and the level of DJ-1 is significantly higher in patients compared to control subjects (Ho, Yi et al 2014). Furthermore, levels of syntenin 1, which is a regulator of EV biogenesis, are greater in EVs isolated from blood of PD patients (Tomlinson, Zheng et al 2015). The discovery of differences in disease-related proteins in EVs isolated from biological fluids of patients and control subjects might lead to early diagnosis and disease prognosis of neurodegenerative disorders.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…Two additional proteins that are linked to PD, DJ-1 and LRRK2 are also detected in EVs isolated from urine samples from PD patients, and the level of DJ-1 is significantly higher in patients compared to control subjects (Ho, Yi et al 2014). Furthermore, levels of syntenin 1, which is a regulator of EV biogenesis, are greater in EVs isolated from blood of PD patients (Tomlinson, Zheng et al 2015). The discovery of differences in disease-related proteins in EVs isolated from biological fluids of patients and control subjects might lead to early diagnosis and disease prognosis of neurodegenerative disorders.…”
Section: Neurodegenerative Disordersmentioning
confidence: 99%
“…Syntenin is among the top 20 proteins most abundantly expressed in the exosomes and epithelial cell cancers (48)(49)(50). Thus, syntenin could serve as a reliable exosome marker.…”
Section: Discussionmentioning
confidence: 99%
“…). In a recent study, MDA‐9/Syntenin was also identified as one of the top 23 proteins differentially expressed in the circulating exosomes of patients with Parkinson's disease (Tomlinson et al, ). Of note, MDA‐9/Syntenin was detected in the exosomes derived from the human melanoma cells and cerebrospinal fluids (Xiao et al, ; Chiasserini et al, ).…”
Section: Mda‐9/syntenin Is a Component Of Cell Adhesion And Ubiquitinmentioning
confidence: 99%